Repurposing medical devices as “button” esophagostomy tubes for extended nutritional support - Melanie D. Craven (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Esophagostomy tubes (E‐tubes) are widely utilized for extended nutritional support in dogs and cats. Problems associated with their use include the unwieldy excess (10‐20 cm) of external tubing, constant need for neck wraps and necessity for skin sutures, suture tract infection, and tube loss if sutures fail. Objectives To evaluate 2 different, low profile (LP) “button” products intended for use in people as enteral (jejunostomy [J] and gastrojejunostomy [G‐J]) feeding tubes for suitability as LP E‐tubes in dogs and cats. Animals A young giant breed dog that required extended (>6 months) nutritional and fluid support during recovery from severe neurological illness with protracted adipsia, anorexia, and dysphagia. Methods Prospective evaluation of 2 commercially available LP feeding devices after placement of a standard E‐tube. An LP J‐tube and an LP G‐J tube were assessed in consecutive 4‐week trials, for tube retention, patient comfort, stoma health, and functionality. Results Both products performed extremely and equally well as LP E‐tubes in this clinical patient, enhancing patient freedom and comfort by eliminating external tubing, skin sutures, and bandaging. The dual port G‐J tube allows medication delivery (eg, sucralfate) to the entire esophagus, but for safety alone (ie, to avoid aspiration), the single port J‐tube appears the best device for client‐owned patients. Conclusions and Clinical Importance The LP enteral feeding tubes from the human medical field can be successfully used as LP E‐tubes in dogs and cats, offering superior patient comfort, with no obvious detriment to the patient and main drawback of higher cost.